2012
DOI: 10.5539/jas.v4n9p150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Population Genetic Structures between Asian and American Mungbean Accessions Using SSR Markers

Abstract: The purpose of this study was to evaluate the genetic diversity and population structure of 65 mungbean accessions collected from East and Southeast Asia, the United States and Guatemala using 15 simple sequence repeat (SSR) markers. In total, 47 alleles were detected, the number of the alleles per locus range from two to six, with an average of 3.13. The mean major allele frequency (MAF), expected heterozygosity (H E ), and polymorphic information content (PIC) of the 15 SSR loci were 0.76, 0.05, and 0.28, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…In the current findings, the highest PIC value is exhibited by G304 (0.3966) in case of green gram followed by MB-SSR 238 (0.3718), G006 (0.3387), G115 (0.2864) and G228 (0.2754). The PIC value of our findings was found to be closely similar to the results of JAYAMANI and SATHYA, 2012; WANG et al, 2012;GUPTA et al, 2013. But the highest marker index (MI) value of 0.3797 and D value of 0.9093 were exhibited by G228 followed by MB-SSR 238 having a MI value of 0.3661 and D Value of 0.8183. In case of green gram, the maximum percentage of polymorphic banding pattern was recorded by G228 followed by MB SSR -28 and G006.…”
Section: Results and Disscussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current findings, the highest PIC value is exhibited by G304 (0.3966) in case of green gram followed by MB-SSR 238 (0.3718), G006 (0.3387), G115 (0.2864) and G228 (0.2754). The PIC value of our findings was found to be closely similar to the results of JAYAMANI and SATHYA, 2012; WANG et al, 2012;GUPTA et al, 2013. But the highest marker index (MI) value of 0.3797 and D value of 0.9093 were exhibited by G228 followed by MB-SSR 238 having a MI value of 0.3661 and D Value of 0.8183. In case of green gram, the maximum percentage of polymorphic banding pattern was recorded by G228 followed by MB SSR -28 and G006.…”
Section: Results and Disscussionsupporting
confidence: 92%
“…It was supported to the earlier result obtained for the discriminating power (D) value and the % of polymorphic banding pattern (Table 4) whereas the PIC value alone did not supported to the results with the % of polymorphic banding pattern (SRIVASTAVA et al, 2011;KANIMOZHI et al, 2009). According to WANG et al (2012), the parameter D not only can be used more efficiently for discrimination of all the cultivars but also for their diversity analysis. Six black gram cultivars of West Bengal were subjected to SSR assay to identify the efficient primers for developing DNA fingerprinting.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…These results indicate that the new KASP-based SNP markers we developed could be useful for future molecular characterization of any other collections of mung bean germplasm. Comparison of the SNP marker information of this study with previous SSR-based genetic diversity studies showed that majority SSR markers had a higher number of alleles per locus and greater PIC values Gwag et al, 2010;Wang et al, 2012;Gupta et al, 2014;Sehrawat et al, 2014;Shrivastava et al, 2014;Chen et al, 2015). Similar results were reported in other species where both SSR and SNP markers were used (Van Inghelandt et al, 2010;Choudhury et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…It is very useful for variety testing and genetic purity. Extensive molecular diversity analysis was done by using different molecular markers using RAPD markers, Sunitha et al, (2012) using 24 ISSR markers and Wang et al, (2012) using 15 SSR markers reported polymorphism in different mungbean genotypes used in their study. Genetic diversity analysis using PCR based markers (RAPD, SSR and ISSR) revealed that, higher marker indices were obtained for ISSR markers, which proved to be the most efficient marker system in terms of average heterozygosity values (Akanksha et al, 2014).…”
Section: Molecular Characterizationmentioning
confidence: 99%